Thursday

April 17, 2014

April 17, 2014

Posted by **Hannah** on Sunday, February 27, 2011 at 9:03pm.

p(x)= (28+x)(8-x/4)

the answer was p=244-7x+8x-x^2/4

p=-x^2/4 + x + 244

p'= -x/2 +1 = 0

X=2

My question is, I do not understand how they got -7x + 8x at the beginning. I know (28)(8)=244 but I do not get the rest.

- Math -
**MathMate**, Sunday, February 27, 2011 at 9:09pmUse FOIL:

(28+x)(8-x/4)

=28*8 -28*x/4 + 8*x -x*x/4

=244 -7x + 8x -x²/4

=244 + x -x²/4

and the rest follows.

- Math -
**Hannah**, Sunday, February 27, 2011 at 9:21pmOh I see. I made a mistake with the 28 (x/4). Thanks!

- Math :) -
**MathMate**, Sunday, February 27, 2011 at 10:22pm:)

**Related Questions**

simple question - If an answer is to be 2 decimal places and the answer is 244....

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 5x...

Math - Solve each equation by completing the square. -36x=8x^2+28 -8x^2-3x=-5 ...

Fundamentals of Taxation - Hamad is an employee of Mountain Company. He properly...

Tax - Hamad is an employee of Mountain Company. He properly completed his Form ...

Tax - Hamad is an employee of Mountain Company. He properly completed his Form ...

income tax - Hamad is an employee of Mountain Company. He properly completed his...

Algebra II - Assume that no denomenator equals 0. (7x^2+3x-9)-(-x^2+8x-3) = 7x^2...

Calculus - another question - "Find the absolute minimum value of the function f...

Math/Algebra - Find each sum or difference (3x^2 + 7x- 2)+ (2x^2 - 3x + 4) ...